Important hypercalcemia due to subcutaneous fat necrosis treated with pamidronate in an infant with severe hypoxic-ischemic encephalopathy - Pasqua Anna Quitadamo; Antonio Villani; Piero Paolo Cristalli; Marina Marinelli; Anita Riganti; Michele Bisceglia; Alberto Gatta (Hygeia Press di Corridori Marinella, 2016)
Subcutaneous fat necrosis (SCFN) of the newborn is an uncommon form of panniculitis that occurs after fetal distress and involves fatty areas during the first weeks of life. This rare disorder is generally self-limiting and undergoes complete regression. However, it can be complicated with a potentially life-threatening hypercalcemia. We report a case of severe hypercalcemia due to SCFN occurring after serious perinatal hypoxic injury, which resolved by intravenous administration of pamidronate. This treatment was rapidly effective and well tolerated. We suggest that pamidronate could be the first-line therapy for severe hypercalcemia in SCFN.